Pendampingan Operator SIIDA untuk Mempercepat Pengisian Data Inovasi dan Meningkatkan Indeks Inovasi Daerah Lampung Selatan - Ari, Ari Kurniawan Saputra; Endra , Robby Yuli; Erlangga, Erlangga; Ariani, Fenty; Kurniawan, Ahmad Shaleh (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2025)
The mentoring activity for the Regional Innovation Index Information System (SIIDA) operators in South Lampung Regency was carried out to strengthen digital-based innovation reporting governance. This activity was motivated by the gap between the number of implemented innovations and those officially reported. The main objective was to enhance the competence of regional government operators in understanding innovation classifications and independently inputting data into the SIIDA platform. The implementation method included socialization, hands-on technical training, data verification, and online monitoring. The results indicated a significant improvement, with reported innovations increasing from 64 to 216 and the reporting index score rising from 0.00 to 91.66, while operators’ comprehension improved from 62% to 88%. The activity proved effective in enhancing the technical capacity of local government staff and strengthening evidence-based innovation reporting. In conclusion, this mentoring model is feasible for sustainable implementation as a strategy to improve regional innovation performance